The Struggle Against Corruption: A Comparative Study - Johnson, R. author. aut Link
XI, 178 p.
Keywords: Understanding and responding to corruption is a worldwide challenge. This book offers a general overview of the nature, pattern, anddiffering perspectives on political and economic corruption. Providing detail and depth, the book examines and compares corruption infour countries: the United States, Israel, Russia, and India. Each country chapter explores how corruption is defined and understood in that country and provides case material illustrating corrupt practice and responses to it. The country chapters also cover whistleblowing activities, their prevalence, importance, and impact. A comparative analysis presents the most prominent factors contributing to a reduced level of corruption and the factors that lead to whistleblower success.